The changing face of the deep: Colonization of the Early Ordovician deep-sea floor, Puna, northwest Argentina - Buatois, Luis Alberto (2009)
An Upper Tremadocian deep-sea ichnofauna from the Chiquero Formation of Puna, northwest Argentina, represents a link between Ediacaran and Cambrian microbial-mat dominated ecosystems and younger Ordovician deep-marine trace-fossil assemblages. This ichnofauna is preserved at the base of thin-bedded turbidites formed in the lobe fringe of a back-arc deep-sea fan. While Ediacaran-Cambrian deep-marine trace fossils are typically linked to matground grazing and feeding, microbial textures in the Chiquero Formation are rare and not associated with trace fossils. Morphologic patterns (e.g. radial trace fossils and networks) of the Chiquero ichnofauna indicate the onset of novel trophic types, recording trapping of microorganisms and bacterial farming. However, in comparison with younger Ordovician deep-sea ichnofaunas, graphoglyptids are relatively rare, poorly diverse, and geometrically simpler. This study indicates that the Early Ordovician was a pivotal point in the ecology of deep-sea infaunal communities. This Upper Tremadocian ichnofauna records the arrival of the Agronomic Revolution to the deep sea. Comparisons with slightly older and younger deep-sea ichnofaunas demonstrate that the colonization of the deep sea was a protracted process spanning the Early Paleozoic, lagging behind colonization of nearshore and offshore substrates.